Antidepressants and driver impairment: empirical evidence from a standard on-the-road test - Ramaekers, Johannes G (The journal of clinical psychiatry, 2003)
The current review summarizes the major results from all published studies from 1983 to 2000 (9 double-blind, crossover, placebo-controlled studies in healthy volunteers and 1 double-blind, baseline-controlled study in patients) that have determined the effects of antidepressants on actual driving performance using a standard test. That test measures driving impairment from vehicular "weaving" (i.e., standard deviation of lateral position [SDLP]) during 1 hour of on-the-road driving in normal traffic. Changes in SDLP after acute doses of sedating antidepressants (i.e., amitriptyline, imipramine, doxepin, and mianserin) were comparable to those seen in drivers conducting the same test with a blood alcohol concentration of 0.8 mg/mL or more. Driving performance of subjects returned to placebo levels after 1 week of treatment, except after treatment with mianserin, for which the impairing effect lasted unabated over treatment. Nocturnal doses of sedating antidepressants (i.e., dothiepin, mianserin, and mirtazapine), however, did not produce residual driving impairment when measured the next day. Nonsedating antidepressants (i.e., moclobemide, fluoxetine, paroxetine, venlafaxine, and nefazodone) generally did not affect SDLP. However, SDLP rose to unacceptable levels after administration of combinations of nonsedating antidepressants and benzodiazepines with incompatible pharmacokinetic profiles. Correlational analyses demonstrated that conventional tests of psychomotor performance or self-ratings of side effects did not strongly predict antidepressant effects on SDLP. Regression analysis revealed a strong linear relation between antidepressant effects in the standard driving test and the number of patients reporting somnolence in clinical trials with the same antidepressants. Application of actual driving tests remains essential to conclusively defining the potential hazard of drugs for driving.